Kewenangan Pemerintah Daerah Dalam Penertiban Penjualan Dana Pada Fasilitas Umum - Leleury, Glenn Michael Pedro; Nendissa, Renny Heronia; Nirahua, Garciano (Faculty of Law, Universitas Pattimura, 2024)
Regional governments have an important role in regulating and supervising activities related to public facilities in their area. PUB practices and the sale of funds are regulated at both national and regional levels. However, the problem from a regulatory perspective is that regulations governing PUB practices in public facilities are often unclear and even inadequate.The purpose of this research is to examine and analyze the authority of regional governments and what forms of control can be carried out by regional governments in controlling the sale of funds in public facility areas. With normative juridical research methods and the nature of descriptive analytical writing.The research results show that:1). The government has the authority to regulate the sale of funds at public facilities, further stated in Law no. 23 of 2014 Article 65 paragraph (1) states that regional heads have the task of